2014
DOI: 10.1159/000368249
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab for Patients with Neovascular Age-Related Macular Degeneration with Good Baseline Visual Acuity

Abstract: Purpose: To report the 1-year results of intravitreal ranibizumab (IVR) injections for neovascular age-related macular degeneration (nAMD) in patients with good baseline visual acuity (VA). Methods: Thirty-six eyes of 36 patients with nAMD with best-corrected VAs (BCVAs) >0.6 (equal to 0.22 in the logarithm of the minimum angle of resolution unit) were enrolled. IVR was the primary treatment; additional treatment was administered as needed. BCVAs and central retinal thickness (CRT) were measured periodically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(38 reference statements)
0
6
0
Order By: Relevance
“… 18 According to Kato et al, mean BCVA in 36 eyes with AMD showed no significant change from 0.11 logMAR at treatment initiation to 0.12 logMAR after 3.3 injections over 12 months. 17 In this study, we treated 39 eyes with AMD. BCVA improved, ranging from −0.08 to 0.26 logMAR (mean 0.097), and from −0.08 to 0.40 logMAR at 12 months (mean 0.058, P =0.03), and was maintained at −0.08 to 0.52 logMAR at 24 months (mean 0.066, P =0.09), after a mean of 6.7±0.72 injections of aflibercept over 12 months and 4.8±1.8 injections from 13 to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“… 18 According to Kato et al, mean BCVA in 36 eyes with AMD showed no significant change from 0.11 logMAR at treatment initiation to 0.12 logMAR after 3.3 injections over 12 months. 17 In this study, we treated 39 eyes with AMD. BCVA improved, ranging from −0.08 to 0.26 logMAR (mean 0.097), and from −0.08 to 0.40 logMAR at 12 months (mean 0.058, P =0.03), and was maintained at −0.08 to 0.52 logMAR at 24 months (mean 0.066, P =0.09), after a mean of 6.7±0.72 injections of aflibercept over 12 months and 4.8±1.8 injections from 13 to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…There were 26 eyes (51.0%) with a logMAR BCVA of 0.15 or less (decimal BCVA of 0.7 or more) in the current study. In the majority of previous prospective studies, patients with a pretreatment decimal BCVA \ 0.5 were included [21], and there were only a few studies that treated patients with AMD including PCV that showed good BCVA [22,23]. Thus, the results of the current study may provide useful information with regard to IVA treatments of PCV patients in clinical practice.…”
Section: Discussionmentioning
confidence: 94%
“…Mori et al [36] performed an average of 4.7 injections of intravitreal ranizbizumab in 50 PCV eyes with a baseline BCVA of 0.6 to 1.0, and reported a significant improvement in BCVA from the baseline (0.11 log-MAR) to 12 months (0.07 logMAR). Kato et al [37] administered intravitreal ranibizumab in PCV with baseline BCVA of 0.10 logMAR. With 3.05 injections, the absolute value of visual acuity improved to 0.09, but there was no statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The size of lesions would be smaller, the activity of the disease would be less severe, damaged retinal tissues that cannot be recovered would be less prevalent in eyes with good visual acuity, and so, the final vision would be better. Table 3 summarizes the BCVA change at 12 months after intravitreal anti-VEGF treatment of previous studies and current study [20,[34][35][36][37][38][39]41].…”
Section: Discussionmentioning
confidence: 99%